Estimating the incidence of rape and sexual assault - Kruttschnitt, Candace (National Academies Press, 2014)
Introduction -- Legal definitions and context -- Data from law enforcement agencies -- National Crime Victimization Survey -- Selected other surveys on rape and sexual assault -- Comparison of rape and sexual assault across data sources -- Potential sources of error in the NCVS : sampling, frame, and processing -- Potential sources of error : nonresponse, specification, and measurement -- Synopsis of potential error in the National Crime Victimization Survey -- New directions for measuring rape and sexual assault